Biosynthesis of ovine recombinant interferon-α in Еsсherichia coli cells - Vostrykava, Krystsina V.; Patapovich, Maksim I.; Prakulevich, Uladzimir A. (Experimental Biology and Biotechnology, 2017)
Viral infection diseases cause huge losses to livestock. Although bacterial infections can be controlled by antibiotics, there is a lack of effective treatment for viral diseases. Recombinant interferons have broad spectrum of antiviral activity and can be used to solve this problem. As a result of the study the ovine interferon-α gene sequence was optimized for expression in gram-negative bacteria and cloned in Еscherichia coli cells as a part of the pET24b vector. A strain producing recombinant ovine interferon-α with a target protein yield of about 40 % of the total cellular protein was obtained.
Keywords: cloning; expression; ovine interferon-α; induction; recombinant protein; mass-spectrometric analysis